2012
DOI: 10.21273/hortsci.47.1.138
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Sunnhemp (Crotalaria juncea L.) on Germination of Vegetables and Weeds

Abstract: Sunnhemp (Crotalaria juncea L.) is a tropical legume that could be an important summer cover crop in the southeastern United States, but it has the potential for suppressing both crops and weeds. Allelopathic effects of sunnhemp on weeds, vegetable crops, and cover crops were evaluated in greenhouse and growth chamber experiments. In the greenhouse, ground dried sunnhemp residues (applied mixed with the soil at 1.6% w/w) reduced percent germination of lettuce (La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 12 publications
1
30
1
10
Order By: Relevance
“…This is not surprising given that plastic mulch effectively inhibits broadleaf weed density (Ashrafuzzaman et al, 2011;Johnson and Fennimore, 2005;Ngouajio and Ernest, 2005). Sunn hemp has been shown to effectively reduce weed populations in many studies (Adler and Chase, 2007;Cho et al, 2015;Javaid et al, 2015;McSorley et al, 2008;Skinner et al, 2012) but it did not have a consistent effect on weed density in the subsequent crop in our research. In Dover, the presence of sunn hump as a cover crop following muskmelon harvest may have effectively reduced establishment of the dominant weeds and prevented their seed production.…”
Section: Resultscontrasting
confidence: 45%
See 1 more Smart Citation
“…This is not surprising given that plastic mulch effectively inhibits broadleaf weed density (Ashrafuzzaman et al, 2011;Johnson and Fennimore, 2005;Ngouajio and Ernest, 2005). Sunn hemp has been shown to effectively reduce weed populations in many studies (Adler and Chase, 2007;Cho et al, 2015;Javaid et al, 2015;McSorley et al, 2008;Skinner et al, 2012) but it did not have a consistent effect on weed density in the subsequent crop in our research. In Dover, the presence of sunn hump as a cover crop following muskmelon harvest may have effectively reduced establishment of the dominant weeds and prevented their seed production.…”
Section: Resultscontrasting
confidence: 45%
“…Sunn hemp is low maintenance and requires no attention after planting until harvest (White and Haun, 1965). Moreover, integration of sunn hemp as a cover crop may reduce weed emergence and growth through release of allelochemicals (Adler and Chase, 2007;Javaid et al, 2015;Skinner et al, 2012). Therefore, the use of sunn hemp in a fallow period may shift the composition of weed seed bank and increase the crop productivity in a rotation program.…”
mentioning
confidence: 99%
“…Another finding that did not go unnoticed is the scarce presence of Fabaceae, only three of the 12 registered by García-Jiménez (2015) for sugar cane cultivation were observed; and this may be related to the fact that C. juncea has been reported as one of the most effective in suppressing the emergence of weeds, due to its rapid growth, competitiveness and allelochemical effect (Skinner et al, 2012), an aspect that is also reflected in the difference found in the species richness when comparing the plots with and without sunn crotalaria.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the continuous pre-harvest sugar cane field burning contributes to weed growth, mainly herbaceous weeds, whose competition is usually very aggressive in the early stages of crop development; occasionally, some woody weeds are also observed, and these plants pose serious problems at any stage, as all of them usually have a great ability to spread out (Valdez-Balero et al, 2009). Severino and Christoffoleti (2004) and Skinner et al (2012) affirm that sunn crotalaria is one of the most effective Fabaceae to suppress weed emergence, given its rapid growth, large production of phytomass, competitiveness and allelochemical effect. Therefore, the present study aimed at assessing the effect of Crotalaria juncea L. on the composition of weed communities and on the production of phytomass in a sugarcane soil under three doses of fertilizer.…”
Section: Introductionmentioning
confidence: 97%
“…Late termination could also inhibit the vegetable root growth due to different causes: inhibitory substances contained in the cover crop biomass, lack of oxygen consumed for biomass demolition, development of diseases (Bath 2000;Skinner et al 2012).…”
Section: Termination Datementioning
confidence: 99%